2022
DOI: 10.30598/barekengvol16iss4pp1411-1422
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Random Forest and Naïve Bayes Methods for Classifying and Forecasting Soil Texture in the Area Around Das Kalikonto, East Java

Abstract: Soil texture is used to determine airflow, heat, instability, water holding capacity, and the shape and structure of the soil structure. Soil texture as an important attribute that determines the direction of soil management must be modeled accurately. However, soil texture is a soil attribute that is quite difficult to model. It is a compositional data set that describes the particle size of the soil mineral fraction (sand, silt, and clay). The methods used to classification and predict soil texture with mach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
1
0
1
Order By: Relevance
“…Random Forest's dependability is applicable in a variety of settings, such as the Internet of Things (IoT) [22]. Previous research [23], [24], [25], [26], [27], has shown that the Random Forest algorithm is reliable when it comes to classification; nevertheless, this study specifically highlights the Random Forest algorithm's use in the context of harmful PDF classification.…”
Section: Machine Learning Classificationmentioning
confidence: 98%
“…Random Forest's dependability is applicable in a variety of settings, such as the Internet of Things (IoT) [22]. Previous research [23], [24], [25], [26], [27], has shown that the Random Forest algorithm is reliable when it comes to classification; nevertheless, this study specifically highlights the Random Forest algorithm's use in the context of harmful PDF classification.…”
Section: Machine Learning Classificationmentioning
confidence: 98%
“…Menurut (Pramoedyo, 2022) Random Forest adalah pengembangan pohon keputusan dengan menggunakan banyak pohon keputusan dimana setiap pohon keputusan telah dilatih menggunakan sampel individu dan setiap atribut dibagi menjadi pohon yang elit antara satu set atribut acak dan setiap atribut dibagi menjadi pohon yang dipilih antara subset atribut acak dan setiap atribut dibagi menjadi pohon yang dipilih antara satu set atribut acak dan setiap atribut Random Forest mungkin merupakan teknik organisasi yang mengumpulkan variabel freelance masih sebagai data sampel, yang mengarah ke pohon klasifikasi dengan berbagai ukuran dan bentuk.…”
Section: Random Forestunclassified